2021
DOI: 10.1186/s12889-021-12008-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with respiratory infectious disease-related presenteeism: a rapid review

Abstract: Background Workplace transmission is a significant contributor to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreaks. Previous studies have found that infectious illness presenteeism could contribute to outbreaks in occupational settings and identified multiple occupational and organisational risk factors. Amid the COVID-19 pandemic, it is imperative to investigate presenteeism particularly in relation to respiratory infectious disease (RID). Hence, this rapid review aims to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 82 publications
0
28
0
3
Order By: Relevance
“…This large fraction of people, who had not undergone self-isolation or quarantine, is likely to have contributed to the transmission of SARS-CoV-2 infection and to the spread of the disease outbreaks in small communities such as households [56] during the most severe restrictions period, or such as workplaces [57] when the restrictions were less stringent.…”
Section: Discussionmentioning
confidence: 99%
“…This large fraction of people, who had not undergone self-isolation or quarantine, is likely to have contributed to the transmission of SARS-CoV-2 infection and to the spread of the disease outbreaks in small communities such as households [56] during the most severe restrictions period, or such as workplaces [57] when the restrictions were less stringent.…”
Section: Discussionmentioning
confidence: 99%
“…This large fraction of people, not undergone self-isolation or quarantine, is likely to have contributed to the transmission of SARS-CoV-2 infection and to the spread of the disease outbreaks in small communities such as households [56] during the most severe restrictions period, or such as workplaces [57], when the restrictions were less stringent.…”
Section: Discussionmentioning
confidence: 99%
“…Other recommendations to prevent influenza in the workplace include advising employees to not work when they are sick and ensuring that sick leave policies and staffing levels encourage sick employees to stay home. Working with symptoms of ILI is common [ 16 , 17 ]. Most studies, which have focused on health care personnel, have identified system-level and sociocultural factors associated with working while ill [ 16 ].…”
Section: Discussionmentioning
confidence: 99%